2015
DOI: 10.1111/pce.12588
|View full text |Cite
|
Sign up to set email alerts
|

Responses of two semiarid conifer tree species to reduced precipitation and warming reveal new perspectives for stomatal regulation

Abstract: Relatively anisohydric species are predicted to be more predisposed to hydraulic failure than relatively isohydric species, as they operate with narrower hydraulic safety margins. We subjected co-occurring anisohydric Juniperus monosperma and isohydric Pinus edulis trees to warming, reduced precipitation, or both, and measured their gas exchange and hydraulic responses. We found that reductions in stomatal conductance and assimilation by heat and drought were more frequent during relatively moist periods, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
113
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 118 publications
(130 citation statements)
references
References 55 publications
(89 reference statements)
12
113
2
Order By: Relevance
“…Furthermore, Meinzer et al [35] evaluated metrics of stomatal regulation of Ψ l during soil drying in eight woody species and assessed whether easily determined leaf pressure-volume traits could serve as proxies for their degree of iso-vs. anisohydric behaviour. According to Garcia-Forner et al [36], and contrary to their expectations, both of these species (J. monosperma and P. edulis) exhibited similar stomatal temporal dynamics in response to drought, with little embolism in J. monosperma due to its conservative stomatal regulation. This contributed to refuting the concept that very low water potentials during drought are associated with loose stomatal control and with the hypothesis that anisohydric species are more prone to hydraulic failure than isohydric species.…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, Meinzer et al [35] evaluated metrics of stomatal regulation of Ψ l during soil drying in eight woody species and assessed whether easily determined leaf pressure-volume traits could serve as proxies for their degree of iso-vs. anisohydric behaviour. According to Garcia-Forner et al [36], and contrary to their expectations, both of these species (J. monosperma and P. edulis) exhibited similar stomatal temporal dynamics in response to drought, with little embolism in J. monosperma due to its conservative stomatal regulation. This contributed to refuting the concept that very low water potentials during drought are associated with loose stomatal control and with the hypothesis that anisohydric species are more prone to hydraulic failure than isohydric species.…”
Section: Introductionmentioning
confidence: 78%
“…; Garcia‐Forner et al . ). Moreover, almost no literature exists on the response of foliar traits to long‐term simultaneous warming and precipitation reduction of mature trees in natural forest ecosystems.…”
Section: Introductionmentioning
confidence: 97%
“…Piñon pine tolerates high temperatures (Spaulding, Robinson & Paillet ) and demonstrates relatively high resistance to water stress (Linton, Sperry & Williams ; Garcia‐Forner et al . ). Here, we tested foliar traits that represent tree physiology (needle emergence, maximum photosynthesis, stomatal conductance, WUE and shoot elongation) and morphology (needle length and thickness, and leaf mass per area (LMA)).…”
Section: Introductionmentioning
confidence: 97%
“…Unlike our findings, however, (Garcia-Forner et al, 2016;Grossiord et al, 2017) found no compounding effect of increased drought in addition to increased temperatures. This discrepancy could simply be the result of differing timescales; while a change in climate might not have a measurable response in vegetation in the short term (such as (Bates et al, 2006) observed in the initial years of their study), or be confounded by previous conditions, this climate pattern can have a large enough effect on tree survival to change species distribution in a climate scenario that has been run until steady state.…”
Section: South-facing Slopescontrasting
confidence: 57%